On the potential of integrating building information modelling (BIM) for the additive manufacturing (AM) of concrete structures. Issue 3 (27th November 2019) - Gradeci, Klodian; Labonnote, Nathalie
Abstract : Purpose: Additive manufacturing (AM) and building information modelling (BIM) are emerging trends for which it has been claimed that both increase both efficiency and productivity in the construction industry. This study aims to synthesise and aggregate the literature addressing BIM integration in the AM of concrete structures and to exploit the joint value creation potential. Design/methodology/approach: This study firstly applies a mixed-review method to achieve mutual corroboration and interdependency between quantitative and qualitative research approaches. Bibliometric mapping is applied to identify, map and synthesise the relevant literature. Scoping review is used to examine the extent, gap, range and nature of the research activity. Afterward, a cross-situational analysis, the threats, opportunities, weaknesses and strengths 2 matrix, is proposed and applied to exploit the joint value creation potential of different aspects of AM and BIM. Findings: The study reveals a substantial interest in this field. However, progress in terms of integration is slow compared to the rapid development in interest in the two trends individually. The literature discusses or conceptualises such integration at building-scale, while prototyping or proof-of-concept processes are only rarely used. The study identified 12 joint value creation potentials through the integration of BIM in AM for concrete structures, which can create value by enabling more optimised designs, automated construction processes and data analytics that can apply throughout the building life-cycle process. Originality/value: The advancements of BIM integration in the AM of concrete structures are analysed and joint value creation potentials are proposed. The study proposes a cross-situation analysis that can be applied to structure joint value creation potentials from the multi-dimensional integration of different factors and topics, especially for emerging technologies.